Company Bankruptcy Relations, Labor Rights, and the National Economy - Alifian Fajar Rizkita; Dicka Pandu Anggara; Muhammad Satrio Bagus Panuntun; Bayu Ajie Sugeng Rahayu; Yan Yulio Anggoro; Muhammad Bagoes Raihan; Tomás Mateo Ramon (Universitas Muhammadiyah Surakarta, 2022)
Bankruptcy is a condition or condition when the debtor, namely a person or business entity, is unable to settle the payment of the debt given by the creditor. This situation is actually a common thing in the business world.In Indonesia, bankruptcy is regulated in Law Number 37 of 2004 concerning bankruptcy and postponement of debt repayment obligations or abbreviated as UUK 2004. Prior to the enactment of the 2004 UUK, the issue of bankruptcy was regulated in Staatsblad 1905:217 jo. Staatsblad 1906:348 concerning Faillissement Verordening (Law on bankruptcy) which was later regulated through Government Regulation in Lieu of Law Number 1 of 1998 and later ratified into Law Number 4 of 1998.Generally, companies go bankrupt because they fail to compete in the market and experience a slow process of innovation. This can be caused by many factors. In addition, with the development of information technology today, new trends and products can appear at any time. All of these things will have an impact on the company's income, profits, financial capabilities and liabilities. Lack of observing competitors' movements can also cause a company to go bankrupt. Companies become less competitive and fall far behind.